Generation of an isogenic CRISPR/Cas9-corrected control induced pluripotent stem cell line from a patient with autosomal dominant catecholaminergic polymorphic ventricular tachycardia with a heterozygous variant in cardiac calsequestrin-2 - Ginell N. Ranpura; Mira Holliday; Serena Li; Samantha B. Ross; Emma S. Singer; Stuart T. Fraser; Richard D. Bagnall; Christopher Semsarian; Seakcheng Lim (Stem Cell Research)
Catecholaminergic polymorphic ventricular tachycardia (CPVT) is an inherited cardiac disease characterised by adrenergic-induced arrhythmias. The leading causes of CPVT are pathogenic variants in cardiac ryanodine receptor 2 (RYR2) and rarely, in cardiac calsequestrin-2 (CASQ2) genes, which are major components of Ca2+ handling in cardiac myocytes. This resource builds upon an established induced pluripotent stem cell line generated from a family with autosomal dominant CPVT due to a heterozygous variant in CASQ2 c.539A > G, p.Lys180Arg (CIAUi003-A) (Ross et al., 2019). The current iPSC line was genetically modified using CRISPR/Cas9 to correct the pathogenic c.539A > G variant creating a CRISPR-corrected isogenic control line (CIAUi003-A-1).